Assessment of the current situation of informal recyclers and recycling: Case study Bogotá (2019)
The contribution of recyclers to the environment and the local economy is not recognized and they are not remunerated for the service they provide to the city. It is well known that informal collection contributes to the recycling of resources in a positive way, but it is also associated with several environmental, health, and social problems. In Colombia, these recyclers work informally. In 2016, Decree 596 was issued, which regulates the utilization of the public cleaning service and the transitory regime for the formalization of informal recyclers. The objective of this work is to evaluate the social and technical impact of recycling in the city of Bogotá three years after the regulations were issued. A study was carried out in order to study how recyclers have been affected by the new regulations after three years of validity as well as understand their perceptions of the evolution of recycling in the city. The study consisted of a series of surveys of recyclers from a statistical sample with 0.05 error that applied a mixed approach. Qualitative and quantitative analysis were included. This analysis was done in order to mix statistical results with deep analysis. The survey indicated that a low percentage of users (good 28%) performed good processes of separation at the source, which lowers the recovery of materials and prevents the potential use of many others. Likewise, it was evidenced that for a material to be sold or commercialized it depends significantly on the separation at the source. In addition, according to the perception of the respondents, society tends to discriminate against them, which leads to the conclusion that discrimination still exists between both the government and society. Finally, the current legislation has not been effective in its implementation and court declarations regarding recyclers as people with inherent rights have not yet been applied in Colombia. © 2019 by the authors.